Predictors for the clinical prognosis of sylvian arachnoid cysts in children - Zhao, Heng; Xie, Wanqun; Cao, Liangliang; Ni, Zhouwen; Wang, Baocheng; Ma, Jie (Frontiers in Pediatrics, 2023)
OBJECTIVES To investigate the influencing factors of clinical prognosis of intracranial sylvian arachnoid cysts(IAC) in children METHODS We retrospectively collected the clinical data of children with IAC admitted to our department from January 2015 to December 2017.The patients were divided into surgery group (279 cases) and non-surgery group (221 cases) according to whether they underwent surgery or not. Then we followed the children for clinical and imaging findings.Then we compared the clinical characteristics and prognosis of children in different groups, and further used multivariate logistic regression to analyze the factors that may affect the prognosis of children. RESULTS 500 patients were successfully followed, and no deaths occurred during follow-up.During the follow-up period, 68 cases had cysts related complications,91 children developed new symptoms during the follow-up period.At the last follow-up, 424 patients had a good prognosis and 76 had a poor prognosis.There were significant differences between the two groups in age, gender, Galassi subtype, whether the mother was a unipara, the maximum diameter of the cysts at the first visit, the maximum diameter of the cysts at the last follow-up, headache, increased head circumference, temporal bulge, new symptoms, cysts rupture and hemorrhage, subdural effusion, and whether the cysts disappeared(P<0.05).Changes in the maximum diameter of the cysts in the surgery group was significantly greater than that in the non-surgery group. Binary logistic regression analysis showed that the number of symptoms (only 1 symptom ), no new symptoms during follow-up, surgery treatment, age group (1-6 years), maximum diameter of cysts (maximum diameter < 5cm) at first diagnosis were independent risk factors affecting the prognosis of children(P<0.05). CONCLUSIONS If the patient is older than 22.5 months, the maximum diameter of the cysts is greater than 5.75cm, has multiple symptoms, has new symptoms during the follow-up, is born prematurely, and has obvious discomfort symptoms after trauma, we recommend that the necessary surgical treatment be performed in time.Complications such as cysts rupture with hemorrhage and subdural effusion during the follow-up period will not have a significant effect on the prognosis of patients after timely treatment. cysts disappearance is not a necessary factor for good prognosis.